Antidiabetic Rosiglitazone Reduces Soluble Intercellular Adhesion Molecule-1 Level in Type 2 Diabetic Patients with Coronary Artery Disease - Guang Wang; Zhe Zhang; Jie Yu; Fuchun Zhang; Liyun He; Jinru Wei; Jieming Mao; Xian Wang (PPAR Research)
Background. We investigated the level of soluble adhesion molecules in diabetic patients and the effect of the peroxisome proliferator-activated receptor-γ (PPAR-γ) agonist rosiglitazone on plasma levels of adhesion molecules and an inflammation marker in type 2 diabetic patients with coronary artery disease (CAD) after percutaneous coronary intervention (PCI). Methods. A total of 116 diabetic patients with CAD who had undergone PCI were randomized to receive rosiglitazone (4 mg/d) or not for 6 months. Plasma levels of soluble intercellular adhesion molecules (sICAM-1) and P-selectin (sP-selectin) were measured on ELISA. Results. After 6-month rosiglitazone treatment, plasma levels of sICAM-1 were lower than baseline and control group levels (370.4 (332.4–421.9) pg/mL versus 423.5 (327.4–500.3) pg/mL and 404.6 (345.2–483.4) pg/mL, P<.001). In addition, plasma levels of C-reactive protein were significantly reduced from baseline levels. However, plasma level of sP-selectin was not significantly lowered with rosiglitazone treatment than with control treatment after 6-month follow-up. Conclusions. Rosiglitazone reduces chronic inflammatory responses and improves levels of markers of endothelial dysfunction in patients with diabetes and CAD. PPAR-γ agonist may have a beneficial effect on the vascular endothelium through its anti-inflammatory mechanism and may be useful as therapy in patients undergoing PCI.